Contrasting patterns of care for musculoskeletal disorders and injuries of the upper extremity and knee through workers' compensation and private health care insurance among union carpenters in Washington State, 1989 to 2008. Issue 9 (4th May 2015) - Lipscomb, Hester J.; Schoenfisch, Ashley L.; Cameron, Wilfrid; Kucera, Kristen L.; Adams, Darrin; Silverstein, Barbara A.
<x xml:space="preserve">Abstract</x> Background Musculoskeletal symptoms and disorders (MSDIs) are common reasons for visits to medical providers in the general population and they are common work‐related complaints. Prior reports raise concerns as to whether declines in workers' compensation (WC) rates represent true improvement in occupational health and safety or shifting of care to other payment systems. Methods By linking administrative records, we compared patterns of WC claims and private health care utilization for disorders of the upper extremity (UE) and knee among a large cohort of union carpenters over a 20‐year period. Results As WC claim rates declined, private health care utilization increased. The increase was muted somewhat but sustained when adjusting for other patterns of health care utilization. Conclusions Findings suggest the decline of WC claim rates do not solely represent improved occupational safety in this population, but also a considerable shifting of care to their private insurance coverage over time. Am. J. Ind. Med. 58:955–963, 2015. © 2015 Wiley Periodicals, Inc.